THE STRATEGIC EFFECTIVENESS OF GAME-BASED LEARNING (GBL) IN TEACHING ENGLISH TO YOUNG LEARNERS, FUNDAMENTAL THEORIES AND EXPERIMENTAL ANALYSIS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This comprehensive scientific article provides a profound analysis of the psycholinguistic, cognitive, and methodological foundations of Game-Based Learning (GBL) in teaching English to preschool and primary school children. The relevance of this research is established by the incompatibility of traditional academic teaching methods with the cognitive nature of young learners, which often results in systemic issues such as "language phobia," classroom disengagement, and a decline in motivation. The study systematically examines the role of game-based instruction in sustaining voluntary attention, facilitating the transfer of new vocabulary into longterm memory at the neural level, and mitigating emotional barriers (the Affective Filter) during the learning process. Results from a two-year comparative experimental study conducted in Uzbekistan's primary schools indicate that student groups utilizing game-based methods achieved a proficiency coefficient 50% higher than that of the control group. The article provides a scientific substantiation for the distribution of Total Physical Response (TPR), digital gamification, and cognitive-didactic games across various lesson stages, grounded in neuropedagogical frameworks.